The acute effects of post-activation potentiation (PAP) warm-up protocols on anaerobic performance and lactate changes in female talo athletes - Hengameh Moradiyan; Abdolhossein Parnow; Rasoul Eslami (Shahid Beheshti University, 2019)
Purpose: Post-activation potentiation (PAP) is a relatively new training technique that positively influence athletes' performance. The purpose of this study was to determine the acute effects of different PAP warm-up protocols on anaerobic performance, and lactate changes in Talo female athletes.Methods: Ten elite Talo female athletes (age 19.9± 3.31, height160 ± 3.7 cm, weight 54.68± 5.18kg, body fat 13.3± 3.37%, Body mass index 21.19± 1.46) participated. They randomly performed one of the three following protocols in consecutive days: A. specific Wushu warm up (specific protocol); B. 2 sets × 2 repetitions back squat with 70%1RM (strength protocol); and C. 40 yard sprint with 0, 10, 20, and 30% of body weight (speed protocol). The RAST test was done 5 minutes after each warm-up protocol. Heart rate (for 10 seconds) and blood lactate (via lactometer) were recorded before and immediately after warm-up, as well as before and immediately after RAST test. For data analyzing, the repeated measures ANOVA and LSD post hoc was used.Results: Results showed a significant difference among the mentioned 4 times of lactate measurement (P<0.001), while there was no significant difference among protocols in a given time (P>0.05). A significant difference between specific and the strength protocols (P=0.002) in case of minimum power, and strength and speed protocols (P=0.ی024) in regard to the fatigue index was observed. Both were in favor of strength protocol. There was no significant difference among the warm-up protocols on peak power and mean power (P>0.05), too.Conclusion: The type of the training performance determines the magnitude of PAP effects. Results indicated PAP probably wouldn't have any efficacy in Talo athletes due to the glycolytic dominant system while probably PAP has more positive effects on speedy and power-explosive athletes.